Family support and hygiene practices in elderly stroke survivors: A study in Aceh - Diantika, Syifara; Saraya, Putri; Yati, Muliati (Indonesian Nursing Journal, 2025)
Background: Stroke significantly impacts elderly individuals’ ability to perform daily activities, including personal hygiene, which is critical for physical health and psychological well-being. In Aceh, Indonesia, family support plays a pivotal role in caregiving, influenced by strong cultural and religious norms. Purpose: This study aims to examine the relationship between family support and personal hygiene practices among elderly stroke survivors in Aceh, exploring how different types of family support influence hygiene outcomes in this unique cultural context. Methods: A cross-sectional correlational design was employed, involving 88 elderly stroke survivors recruited through purposive sampling from healthcare and community settings in Aceh. Data on family support (emotional, instrumental, and informational) and personal hygiene practices were collected using structured questionnaires. Analysis was conducted using descriptive statistics, Pearson’s correlation, and regression analysis to identify associations between variables. Results: The findings indicate that higher levels of family support are positively correlated with improved personal hygiene practices (r = 0.65, p < 0.01). Emotional, instrumental, and informational support emerged as significant predictors of hygiene outcomes, with instrumental support showing the strongest impact (β = 0.45, p < 0.01). Additionally, demographic factors such as education level and socio-economic status were associated with variations in family support levels and hygiene practices. Conclusion: Family support, particularly instrumental assistance, is essential for promoting personal hygiene among elderly stroke survivors. Interventions to strengthen family caregiving capacities should consider Aceh’s socio-cultural dynamics and integrate community-based and educational programs to improve outcomes. These findings provide actionable insights for culturally sensitive stroke rehabilitation strategies in resource-limited settings.